About the forbidden laughter - Stillmark, Hans-Christian (Transfer. Reception Studies, 2020)
The essay explores the question of what happens in forbidden contexts when laughter cannot be suppressed. A childhood experience is the occasion to reflect on the communicative relations of forbidden laughter. Laughter is pointed out as a special communica-tive sign system and physical act.